Analisis Parameter Fisik-Kimia Air Sungai Kadia pada Tahun Pertama Pandemi COVID-19 di Kota Kendari - Sumarlin Sumarlin; Suherman Suherman; Moch. Assidieq (Fakultas Teknik, 2021)
The high risk of the Coronavirus disease (COVID-19) pandemic has caused the government set a various of policies to limit citizen mobility. The imposition of this mobility restriction has a significant impact on the environment. This study aims to analyze several physic-chemical waters parameters in Kadia River during the first year of the COVID-19 pandemic. The results of this study indicate that temperature, turbidity, DO at low tide and BOD exceed the required quality standard. The contribution of household domestic waste is very likely to have an effect on the height of some of these parameters, because in the first-year people are more active at home (work from home). The other parameters (DHL, pH, NO2, PO4) are still within the quality standard threshold level. Therefore, it is necessary to control and manage waste water from urban domestic so that the sustainability of river ecosystems can continue in the future.